Characteristics and Correlates of Cyber-control in Spanish Cases of Gender-Based Violence - Niehaus, Kory; Fontao, María Isabel; Garrido Antón, María José; Quevedo-Blasco, Raúl (Anales de Psicología / Annals of Psychology, 2025)
This explorative study aimed to identify the psychosocial characteristics of the perpetrator and the victim, as well as the relationship dynamics and different forms of control and violence associated with cyber-control. Analyses were conducted retrospectively on a dataset of N = 368 cases of fatal and non-fatal gender-based violence, collected by the EHVdG (National Team for In-Depth Homicide Review of Gender Violence) between 2006 and 2021 in Spain. Mean comparison procedures were performed between cases with and without cyber-control, as well as binomial logistic regression analyses, to identify correlative and predictive associations. Cyber-controlled relationships were characterized by an insecure-anxious attachment style of the perpetrator, a lower age of both partners, isolation, jealousy, and a shorter relationship duration. No predictive associations could be confirmed. Cyber-control co-occurred with several violent and controlling behaviors. Due to this co-occurrence, cyber-control should be considered an alarm signal for other forms of gender-based violence. The correlates identified could be a starting point for possible interventions.